Fecal microbiota transplantation: therapeutical approaches and regulatory framework - A. N. Vasilyev; D. V. Goryachev; E. V. Gavrishina; R. R. Niyazov; Yu. A. Seliverstov; A. V. Digtyar (Биопрепараты: Профилактика, диагностика, лечение)
Since Ilya Metchnikoff’s studies, both medical science and clinical practice have accumulated a large amount of evidence that human intestinal microbiota possesses a unique characteristics for our existence. However, only recently, scientists have achieved the actual breakthrough in this field of human physiology, and we start to understand the precise mechanisms of the complex interplay of microbial activity with human homeostasis and discover numerous new functions of intestinal microbes. In this regard, a novel medical technology evolves since 1958, so called fecal microbiota transplantation (FMT), which is the administration of donor feces to the patients suffering from different kinds of diseases. Such infusion of donor feces restores the natural balance of gut commensal germs. FMT is most efficacious in severe or recurrent Clostridium difficile infection. FMT has been also reported to cure diarrhea and constipation caused by different conditions, such as multiple sclerosis, Crohn ’s disease etc. In the U.S. and Canada as well as in other countries FMT is of uttermost interest of not merely clinical practitioners but lately also of regulatory authorities. The paper also addresses the possibility of application the Russian pharmaceutical legislation to FMT.